2021
DOI: 10.1155/2021/2826609
|View full text |Cite
|
Sign up to set email alerts
|

Identification of KLF6/PSGs and NPY-Related USF2/CEACAM Transcriptional Regulatory Networks via Spinal Cord Bulk and Single-Cell RNA-Seq Analysis

Abstract: Background. To further understand the development of the spinal cord, an exploration of the patterns and transcriptional features of spinal cord development in newborn mice at the cellular transcriptome level was carried out. Methods. The mouse single-cell sequencing (scRNA-seq) dataset was downloaded from the GSE108788 dataset. Single-cell RNA-Seq (scRNA-Seq) was conducted on cervical and lumbar spinal V2a interneurons from 2 P0 neonates. Single-cell analysis using the Seurat package was completed, and marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…With the establishment and development of single-cell genome sequencing, the understanding of diseases and the analysis of genomic features have entered the single-cell level [ 12 , 13 ]. Single-cell sequencing technology is a powerful tool for studying cellular heterogeneity since it can reveal the gene structure and expression status of individual cells [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the establishment and development of single-cell genome sequencing, the understanding of diseases and the analysis of genomic features have entered the single-cell level [ 12 , 13 ]. Single-cell sequencing technology is a powerful tool for studying cellular heterogeneity since it can reveal the gene structure and expression status of individual cells [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of single-cell sequence technologies has allowed previous studies to collect gene expression data at the single-cell level in recent years ( 20 24 ). The analysis of single cells can identify the mechanisms of cellular interactions and is essential for establishing the molecular regulation of diseases at the microscopic level ( 25 28 ). Single-cell RNA sequencing analysis revealed that megakaryocytes and a few monocyte subpopulations may significantly elevate cytokine levels in patients with severe coronavirus disease 2019 ( 29 ).…”
Section: Introductionmentioning
confidence: 99%